2018
DOI: 10.1098/rsos.171506
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure of Hawaii Island spinner dolphins (Stenella longirostris) to human activities

Abstract: Habitat selection is strongly influenced by spatial variations in habitat quality and predation risk. Repeated exposure of wildlife to anthropogenic activities in important habitats may affect habitat selection, leading to negative biological consequences. We quantified the cumulative human exposure of a small, genetically isolated and behaviourally constrained spinner dolphin (Stenella longirostris) population, off Hawaii Island, and exposure effects on their daytime cumulative activity budget. Dolphins were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 67 publications
1
29
0
1
Order By: Relevance
“…It is often difficult to correlate short-term behavioral changes with long-term negative outcomes on the biology and ecology of targeted populations, however, there is growing evidence that repetitive short-term behavioral changes, induced by frequent disturbance, can influence life functions (i.e., feeding, predator response, migration and breeding) by imposing additional costs on the energetic budget of individuals (Christiansen, Rasmussen & Lusseau, 2013;Senigaglia et al, 2016;Noren et al, 2016). Tour boat disturbance has been linked to shifts in the activity budgets of numerous cetacean species (Williams, Lusseau & Hammond, 2006;Meissner et al, 2015;Pérez-Jorge et al, 2016;Tyne et al, 2018). These studies indicate that short-term avoidance tactics used by individuals can exert a cumulative effect on animals by altering activity budgets and potentially increasing energetic costs.…”
Section: Introductionmentioning
confidence: 99%
“…It is often difficult to correlate short-term behavioral changes with long-term negative outcomes on the biology and ecology of targeted populations, however, there is growing evidence that repetitive short-term behavioral changes, induced by frequent disturbance, can influence life functions (i.e., feeding, predator response, migration and breeding) by imposing additional costs on the energetic budget of individuals (Christiansen, Rasmussen & Lusseau, 2013;Senigaglia et al, 2016;Noren et al, 2016). Tour boat disturbance has been linked to shifts in the activity budgets of numerous cetacean species (Williams, Lusseau & Hammond, 2006;Meissner et al, 2015;Pérez-Jorge et al, 2016;Tyne et al, 2018). These studies indicate that short-term avoidance tactics used by individuals can exert a cumulative effect on animals by altering activity budgets and potentially increasing energetic costs.…”
Section: Introductionmentioning
confidence: 99%
“…The common natural environments include water, atmosphere, sunlight, soils, and mountains [1]. The research subjects of natural environments mainly include the climate [2], weather [3], water resources [4], animals and plants [5], agroforestry [6], geomorphology [7], and landforms [8]. Researchers have explored the relationship between the natural environment and marathon running from different perspectives, such as the feasibility of marathon running in different natural environments, Chang et al found that the marathon can be held in combination with local environmental advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Bent dorsal fins should be used in assessing the health of a population because, even at low rates, this condition could impact populations such as the endangered false killer whales, of which there are an estimated 150 to 200 in the Main Hawaiian Islands (Bradford et al, 2018), or spinner dolphins, which are facing increasing pressures from high levels of human activity (Tyne et al, 2018). Our observations of an individual surviving 16 years with a bent dorsal fin suggest these disfigurements are not necessarily fatal but could affect an animal's ability to swim, forage, and reproduce (Rommel et al, 1993;Baird & Gorgone, 2005), even when individuals can survive the initial injury.…”
Section: Discussionmentioning
confidence: 99%